Archetypal Deconstruction In Mahasweta Devi’s “Draupadi” - Sharma, Ritu (International Journal of Engineering and Technology, 2018)
Archetypes are tall those images, characters, symbols  and stories that recurnumerable times in the works of literature, andlater transformed into collective prototypes. As per M. H. Abrams and Geoffrey Harpham:“The term archetype denotes recurrent narrative designs of action, character types, themes, and images which are identifiable in a wide variety of works of literature, as well as in myth, dreams and even social rituals”.The Archetypal representation of the tribal women in Mahasweta Devi’s Draupadi has been reviewed and reassessed in the paper along with the reference of the Ancient Draupadi depicted in the great epic Mahabharata. The attempt here is to find the ‘Aboriginal Women’ question while looking at women’s suffering in the past in the present. ‘Draupadi’ by Mahasweta Devi attempts at the Deconstruction and Reconstruction of the episode of cheelharn by Duryodhan in the great epic Mahabharata. The present paper analysis the myth and showcases how Archetypes have been significant in recasting the early tradition and creates a glorious history for women as an act of survival.